Biology of Aganaspis daci (Hymenoptera: Figitidae), parasitoid of Ceratitis capitata (Diptera: Tephritidae): Mode of reproduction, biological parameters and superparasitism - De-Pedro, Luis; Tormos, José; Asís, Josep D.; Sabater-Munoz, Beatriz; Beitia, Francisco J. (2019)
Biological parameters of parasitoid wasps have a decisive effect on their effective performance as biological control agents. The mode of reproduction, several mating-dependent biological parameters (such as longevity, fertility, percentage parasitism, induced mortality and population reduction) as well as superparasitism of the parasitoid Aganaspis daci (Weld) infesting larvae of the medfly Ceratitis capitata (Wiedemann) were assessed under laboratory conditions. The results indicated an arrhenotokous haplodiploid mode of reproduction, with unmated females producing only males and mated females producing a female-biased offspring (female female/(female female + male male) = 0.73) ratio from the first day of life. Additionally, positive mating status showed a significant negative effect on longevity (14-22 days), but no significant differences on fertility, percentage parasitism, induced mortality or population reduction between mated and unmated females. A strong effect of the age of females on fertility and percentage of parasitism was also found, with both decreasing with increasing female age and a similar oviposition pattern for mated and unmated females. Our findings showed the occurrence of superparasitism in this species, with a significant negative effect of host abundance and a significant positive effect of parasitoid (conspecific females) abundance on superparasitism rate. The existence of self-superparasitism was confirmed for females acting alone, whilst female aggregation led to a higher intensity (up to eight eggs/host pupa) and percentage of, presumably, conspecific superparasitism. The information reported here on several biological aspects of A. daci infesting C. capitata supports the use of this parasitoid in biological control programmes against medfly and highlights the importance of several factors, such as the sex ratio or the parasitoid/host ratio under rearing and field conditions, when planning mass production and field releases of this parasitoid.